2021
DOI: 10.1093/cid/ciab549
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline by the Infectious Diseases Society of America (IDSA) and Society for Healthcare Epidemiology of America (SHEA): 2021 Focused Update Guidelines on Management of Clostridioides difficile Infection in Adults

Abstract: This clinical practice guideline is a focused update on management of Clostridioides difficile infection (CDI) in adults specifically addressing the use of fidaxomicin and bezlotoxumab for the treatment of CDI. This guideline was developed by a multidisciplinary panel representing the Infectious Diseases Society of America (IDSA) and the Society for Healthcare Epidemiology of America (SHEA). This guideline is intended for use by healthcare professionals who care for adults with CDI, including specialists in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
286
0
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(386 citation statements)
references
References 35 publications
2
286
0
19
Order By: Relevance
“…In recent years, however, guidelines, such as those published by the IDSA and SHEA, have recommended initial fidaxomicin (preferred) or vancomycin (alternative) over metronidazole for the treatment of non-severe CDI. 5 Our findings support the recommendation to use vancomycin when fidaxomicin is unavailable, which is applicable to institutions that rely on metronidazole and vancomycin for the treatment of CDI. A strength of our investigation was the long duration of follow-up, 26 weeks in a pragmatic real-world setting, which allowed for conclusions about the impact of initial vancomycin treatment on new incident infection, defined as a CDI episode occurring >8 weeks after the initial infection.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In recent years, however, guidelines, such as those published by the IDSA and SHEA, have recommended initial fidaxomicin (preferred) or vancomycin (alternative) over metronidazole for the treatment of non-severe CDI. 5 Our findings support the recommendation to use vancomycin when fidaxomicin is unavailable, which is applicable to institutions that rely on metronidazole and vancomycin for the treatment of CDI. A strength of our investigation was the long duration of follow-up, 26 weeks in a pragmatic real-world setting, which allowed for conclusions about the impact of initial vancomycin treatment on new incident infection, defined as a CDI episode occurring >8 weeks after the initial infection.…”
Section: Discussionsupporting
confidence: 80%
“…In recent years, however, there has been a shift to initial vancomycin to treat first-episode non-severe CDI at our institution, which is consistent with guidelines published by the Infectious Diseases Society of America (IDSA) and Society for Healthcare Epidemiology of America (SHEA), when fidaxomicin is unavailable. 5 Importantly, guidelines published by the European Society of Clinical Microbiology and Infectious Diseases, the World Society of Emergency Surgery, and the Australasian Society of Infectious Diseases still recommend the use of metronidazole for the first episode of non-severe disease. [6][7][8] Although initial fidaxomicin or vancomycin treatment is recommended by most major guidelines to treat severe CDI, there exists a discrepancy in treatment recommendations for firstepisode non-severe CDI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the comparative efficacy of fidaxomicin vs. vancomycin we conducted a metaanalysis of the three double blind, placebo-controlled, randomized controlled trials identified by IDSA-SHEA 8 wherein fidaxomicin was compared head-to-head with vancomycin [3][4][5] . We excluded a fourth trial which was open label and compared a longer total duration of fidaxomicin (30-days vs. 10-days in all other included studies) 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Additional benefits of fidaxomicin include a narrower spectrum of activity, less frequent dosing, and rarity of resistance [ 33 ]. IDSA 2021 updated guidelines specifically address the use of fidaxomicin in adults, now recommending its use for both the first episode of C. difficile , and now also in recurrent episodes over vancomycin [ 34 •]. An extended pulsed regimen of fidaxomicin, like for vancomycin, is also suggested.…”
Section: New Developments In Treatment Options and Future Directionsmentioning
confidence: 99%